A Framework for Discussing e-Research Infrastructure Sustainability. Issue 1 (9th July 2014) - Katz, Daniel S.; Proctor, David
E-Research infrastructure is increasingly important in the conduct of science and engineering research, and in many disciplines has become an essential part of the research infrastructure. However, this e-Research infrastructure does not appear from a vacuum; it needs both intent and effort first to be created and then to be sustained over time. Research cultures and practices in many disciplines have not adapted to this new paradigm, due in part to the absence of a deep understanding of the elements of e-Research infrastructure and the characteristics that influence their sustainability. This paper outlines a set of contexts in which e-Research infrastructure can be discussed, proposes characteristics that must be considered to sustain infrastructure elements, and highlights models that may be used to create and sustain e-Research infrastructure. We invite feedback on the proposed characteristics and models presented herein.